BROWBIE : DIVERSIFIKASI PRODUK UBI SEBAGAI SARANA PENINGKATAN NILAI JUAL MAKANAN TRADISIONAL - Aisah, Dewi Nur; Ananta, Joanna Patricia; Nabilla, Shalsa Yulia; Palguni, Meilia Isnantoro; Ananda, Bella Prima Ria; Priambada, Lingga Arya; Handayani, Langlang (Jurnal Pengabdian dan Kewirausahaan, 2024)
Culinary is a form of culture that continues to develop along with the times. An increasingly popular trend is the use of local ingredients in food preparation. This article discusses innovation in making brownies with Cilembu sweet potato as the main ingredient. Cilembu sweet potato is a type of sweet potato that is popular in Indonesia because it has a sweet taste and soft texture. The use of cilembu sweet potatoes as a basic ingredient in making brownies is an innovation in the development of processed food products. The research method used was experimentation with variations in the composition of ingredients to get the best formula. In addition, the addition of Cilembu sweet potato also increases the nutritional value of brownies with high fiber content.